Kinetic study on the pyrolysis behavior of Huadian oil shale via non-isothermal thermogravimetric data. (15th April 2015) - Bai, Fengtian; Guo, Wei; Lü, Xiaoshu; Liu, Yumin; Guo, Mingyi; Li, Qiang; Sun, Youhong
Highlights: Pyrolysis kinetic behavior of oil shale was investigated. Double-stage parallel reaction model was used for exploring pyrolysis kinetics. The bi-Gaussian method was introduced for fitting DTG curve. Model free methods and master plots were used to determine the kinetic parameters. Results showed the inherent property and thermal stability of oil shale pyrolysis. Abstract: Oil shale pyrolysis is normally extremely complicated because many reactive processes simultaneously occur and different products are therefore continuously generated and serve as a new reactant, as a multi-stage processes with competing or parallel reactions. To probe deeply into the pyrolysis kinetics of Huadian oil shale, we have employed multi-stage parallel reaction model and bi-Gaussian distribution method to fit the non-isothermal thermogravimetric data. Friedman, Flynn–Wall–Ozawa, and Kissinger–Akahira–Sunose methods were utilized to estimate activation energy, and two master plots methods were introduced to establish kinetic models. Two reactions were involved in devolatilization of organic matter in oil shale, and the Reaction II was a principal process of Stage II and dominated kinetic property of overall Stage II. The heating rate had some impact on the pyrolysis process but exerted little influence on kinetic parameters. The comparison of these results indicated the inherent property and thermal stability of oil shale pyrolysis.